IMPACT OF WBC COUNT ON ADMISSION ON EARLY AND LONG-TERM MORTALITY IN PATINETS TREATED WITH PRIMARY PERCUTANEOUS CORONARY INTERVENTION - Starčević, Jovana; Matić, Dragan (Medicinski podmladak, 2022)
ABSTRACTIntroduction: Inflammation plays a key role in the process of atherosclerosis, its formation, progression and destabilization of plaque. One of the main mediators of inflammation are white blood cells (WBC), which number increases significantly during inflammation.Aim: The aim of this study was to determine the effect of WBC count at admission on early and long-term mortality in patients with ST segment elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (PCI).Material and methods: A total of 700 consecutive STEMI patients admitted for primary PCI were included in our study. The patients included in the study were divided into two groups:  group with normal and group with elevated WBC count. A leukocyte count >11000 / mm3 was considered elevated. Patinets were followed-up at 30-days and at 1-year after enrollment.Results: Of the 700 STEMI patients treated with primary PCI, 665 had WBC count data available at admission and were included in further analysis. Of this number, elevated WBC count were registered in 380 patients (57.14%). Patients with increased WBC count were younger  and smokers. Observing the characteristics of patients at admission, patients with elevated WBC count had a lower ejection fraction, higher CPK values ​​as well as a higher incidence of heart failure. Thirty-day as well as 1-year mortality were significantly higher in patients with elevated WBC count. Patients with elevated WBC count were at three-fold higher risk for 30-day mortality and at two-fold higher risk for 1-year morality.Conclusion: Patients with elevated WBC counts at admission had higher 30-day and 1-year mortality compared with patients with normal WBC counts. WBC count was an independent predictor of thirty-day and one-year mortality.Keywords: white blood cell count, ST segment elevation myocardial infarction, primary percutaneous coronary intervention.
Keywords: white blood cell count, ST segment elevation myocardial infarction, primary percutaneous coronary intervention.